Menanamkan Kesadaran Cinta Lingkungan Pada Siswa Sekolah Dasar Negeri Jetis 2 Kabupaten Bondowoso - Akham, Qornan Hafidhul; Arifqi, Muhamad Ali Ibrahim; Setiawan, Bagus Adi; Yusuf, Zahrah Mufidah; Afifurrohman, Ahmad Fata; Rizal, Ahmad; Puspito, Agung Nugroho (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This social project aims to instill a sense of love for the environment from an early age in Elementary School 02 Jetis, Bondowoso Regency. This project uses a qualitative approach and descriptive material presentation. This project was implemented at SDN Jetis 2, Bondowoso Regency with the research subjects being students in grades 4 and 5. Data collected through quiz methods, material presentation, filling out questionnaires, and direct practice with students. Data analysis was carried out through 3 stages, namely data collection, data analysis and conclusions by the implementing team applying a simple approach, starting from joint introductions, storytelling, presenting materials, showing videos about the negative impacts of waste and waste processing, practicing making crafts and compost from organic waste. Activities have a positive impact on students, especially grades 4 and 5, referring to the results of the posttest... social projects that have an impact on enriching environmental insight can be used as an example for further social projects.